(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
The global processes taking place in the world require a harmonious approach to the issue of a person’s mental and physical health. In modern medical practice, solutions to existing problems can be found through medical and spiritual treatments based on religious teachings. The teachings of Christianity and Islam, which are considered world religions, have developed guidelines for regulating not only the spiritual but also the medical health of a person and have been implementing them for many millennia of history. In the context of the 2019 global pandemic related to COVID-19, the popularization of mental and psychological treatment (والنفسية الروحية (processes along with medical treatment has increased the importance of religious medicine. In this regard, studying their religious and social foundations regarding human health issues is of urgent importance.